Technical feasibility assessment of mini-hydropower development at selected sites in the Highlands of Ethiopia - Abera, Wuletawu; Woldearegay, Kifle; Tamene, Lulseged D. (2022)
Renewable energy sources are climate- and land-resource-smart development interventions. In Ethiopia, because of its topographic nature and high rainfall availability, mini-hydropower (MHP) is one of the most suitable renewable energy sources. However, it is variable in space and time, thus requiring accurate estimations regarding its potential for targeting investment. Because of a lack of discharge data and high resolution topographic data, and also because most MHP sites are located in remote areas, the necessary information for developing MHP plants is not readily available. CIAT and Mekelle University, in collaboration with GIZ, conducted a technical feasibility study of some selected proposed sites in Amhara and Oromia regions of Ethiopia. To obtain the necessary information, an intensive field survey and hydrological modeling were conducted. The two important parameters for estimating power (head and discharge) were calculated from a field theodolite leveling survey and hydrological modeling at designated locations. The MHP component layout and geotechnical and basic socioeconomic information have also been documented for the 15 proposed MHP sites.